Profiling of H3K4me3 and H3K27me3 and Their Roles in Gene Subfunctionalization in Allotetraploid Cotton - Zhang, Aicen; Wei, Yangyang; Shi, Yining; Deng, Xiaojuan; Gao, Jingjing; Feng, Yilong; Zheng, Dongyang; Cheng, Xuejiao; Li, Zhaoguo; Wang, Tao; Wang, Kunbo; Liu, Fang; et al. (Frontiers in Plant Science, 2021)
Cotton is an excellent model for studying crop polyploidization and domestication. Chromatin profiling helps to reveal how histone modifications are involved in controlling differential gene expression between A and D subgenome in allotetraploid cotton. However, the detailed profiling and functional characterization of broad H3K4me3 and H3K27me3 are still understudied in cotton. In this study, we conducted H3K4me3 and H3K27me3-related ChIP-seq followed by comprehensively characterizing their roles in regulating gene transcription in cotton. We found that H3K4me3 and H3K27me3 exhibited active and repressive roles in regulating expression of genes between A and D subgenome, respectively. More importantly, H3K4me3 exhibited enrichment levels, positioning and distance-related effects on expression levels of related genes. Distinct GO term enrichment occurred between A and D-specific genes and homeologous genes with broad H3K4me3 in promoters and gene bodies, suggesting that broad H3K4me3-marked genes might have some unique biological functions between A and D subgenome. An anticorrelation between H3K27me3 enrichment and expression of homeologous genes was more pronounced in A subgenome relative to D subgenome, reflecting distinct enrichment of H3K27me3 in homeologous genes between A and D subgenome. In addition, H3K4me3, H3K27me3 marks can indirectly influence gene expression through TF-mediated regulatory networks. Thus, our study provides detailed insights in functions of H3K4me3 and H3K27me3 in regulating differential gene expression and subfuncationalization of homeologous genes, therefore serving a driving force for polyploidization and domestication in cotton.